RELASI GENDER DALAM INSTITUSI KELUARGA (Pandangan Teori Sosial Dan Feminis) - Aisyah, Nur (IAIN Pekalongan, 2013)
Abstract : This study departs from the reality of gender relations within the family institution which has to be dikhotomis, causing the pole inequality relations between men and women. Therefore, in this study wanted to dismantle the detail view of some theories, both social and feminist about gender relations in the family. Each of these theories (structural functional, conflict and feminist) has their own viewpoint about the pattern of gender relations in the family. However, simultaneously acknowledging that the social construction of culture remained significant influence on the division of roles are played by men (husbands) and women (wife) in the family institution. This means that the social construction of culture was instrumental in the creation of relations contribute between men and women equally or otherwise occurred inequality. Abstrak : Penelitian ini berangkat dari realitas hubungan gender dalam institusi keluarga yang harus dikhotomis, menyebabkan hubungan ketimpangan tiang antara laki-laki dan perempuan. Oleh karena itu, dalam penelitian ini ingin membongkar tampilan detail dari beberapa teori, baik sosial dan feminis tentang relasi gender dalam keluarga. Masingmasing teori ini (struktural fungsional, konflik dan feminis) memiliki pandangan mereka sendiri tentang pola hubungan gender dalam keluarga. Namun, secara bersamaan mengakui bahwa konstruksi sosial budaya tetap berpengaruh signifikan terhadap pembagian peran yang dimainkan oleh laki-laki (suami) dan perempuan (istri) dalam institusi keluarga. Ini berarti bahwa konstruksi sosial budaya sangat berperan dalam penciptaan hubungan berkontribusi antara laki-laki dan perempuan sama-sama atau terjadi ketimpangan.